Quartz grinding specific rate of breakage (Sj) classification by discriminant analysis - Laura Colorado-Arango; Sindy Llano-Gómez; Adriana Osorio-Correa (Revista UIS Ingenierías, 2020)
Specific rate of breakage (Sj) is an important parameter for grinding kinetics behavior due to it is reverse related with the process energy consumption. Size grinding media, viscosity medium, and fine particle formation are some of modifiable variable for to reduce the energy in the grinding process. Nowadays, there is no model that explains the relationship among Sj and parameters described above. A classification model based on linear discriminant analysis for quartz wet grinding was proposed to identify conditions with the high Sj. Three grinding kinetic behavior groups have been found through cluster analysis and two discriminant functions that explicate difference among groups. The first function was the most powerful differentiating dimension with 89.01% of prediction percentage, and the second one represented an additional significant dimension with 10.99% of prediction.